Does voter turnout affect the votes for the incumbent government? - Martins, Rodrigo (2013)
This paper analyzes the effects of voter turnout on the vote shares received by the incumbent government. A system of simultaneous equations is estimated using a panel dataset of 278 Portuguese municipalities, for the period 1979-2005, covering 10 legislative elections. The results indicate that right-wing governments have lower vote shares when turnout is higher, while left-wing ones seem to be unaffected. There is also evidence of the responsibility hypothesis, that turnout is higher in closer elections, and that regional/local economic variables have non-linear effects on turnout.